A stringent upper limit on dark matter self-interaction cross-section from cluster strong lensing. Issue 1 (12th November 2021) - Andrade, Kevin E; Fuson, Jackson; Gad-Nasr, Sophia; Kong, Demao; Minor, Quinn; Roberts, M Grant; Kaplinghat, Manoj
ABSTRACT: We analyse strongly lensed images in eight galaxy clusters to measure their dark matter density profiles in the radial region between 10 kpc and 150 kpc, and use this to constrain the self-interaction cross-section of dark matter (DM) particles. We infer the mass profiles of the central DM haloes, bright central galaxies, key member galaxies, and DM subhaloes for the member galaxies for all eight clusters using the qlens code. The inferred DM halo surface densities are fit to a self-interacting dark matter model, which allows us to constrain the self-interaction cross-section over mass σ/ m . When our full method is applied to mock data generated from two clusters in the Illustris-TNG simulation, we find results consistent with no dark matter self-interactions as expected. For the eight observed clusters with average relative velocities of 1458_-81^+80 km s −1, we infer σ /m = 0.082_-0.021^+0.027 cm^2 g^ -1 and σ /m 0.13 cm^2 g^ -1 at the 95 per cent confidence level.